PENDIDIKAN ISLAM ANAK USIA DINI DALAM PERSPEKTIF NEUROSAINS: ROBOTIK, AKADEMIK, DAN SAINTIFIK - Suyadi, Suyadi (Program Studi Pendidikan Agama Islam, 2018)
Abstract Early Childhood Islamic Education (PIAUD) in Yogyakarta is faced with political and academic and even theological dilemmas. On the one hand, PIAUD is required by the community to conduct reading, writing and numeracy (Calistung) reading, including Read Al-Qur'an (BTAQ), but on the other hand the Directorate General (Dirjen) of PAUD prohibits it. The purpose of this study is to describe the types of learning calistung and BTAQ in Yogyakarta in the study of neuroscience, both from the side of teachers, students, learning materials, strategy and evauasi. This research was conducted throughout 2017 involving nine PIAUD institutions in Yogyakarta. The research approach used is qualitative with data collection techniques in the form of interview, observation and documentation. The collected data are analyzed descriptively, interpretatively, and comparative based on neuroscience learning theories. The results showed that PIAUD in Yogyakarta can be placed into three, namely PIAUD robotik, academic and scientific. PIAUD robotik is PIAUD at risk of damaging the brains of children for doing the malls of learning practices (calistung & BTAQ). Academic early childhood is PIAUD risky membonsai brain of children because all learning activities only oriented to the mastery of calistung and memorizing Alqur'an. PIAUD Scientific is PIAUD oriented to the optimization of brain potential of children, because all learning activities are structured based on the characteristics of development and workings of the child's brain. Abstrak Pendidikan Islam Anak Usia Dini (PIAUD) di Yogyakarta dihadapkan pada dilema politis dan akademis bahkan teologis. Di satu sisi PIAUD dituntut masyarakat untuk menyelenggarkan pemebelajaran membaca, menulis dan berhitung (Calistung), termasuk Baca Tulis Al-Qur’an (BTAQ) namun di sisi lain Direktorat Jenderal (Dirjen) PAUD melarangnya. Tujuan penelitian ini adalah mendiskripsikan tipe-tipe pembelajaran calistung dan BTAQ di Yogyakarta dalam kajian neurosains, baik dari sisi guru, siswa, materi pembelajaran, strategi dan evauasi. Penelitian ini dilakukan sepanjang tahun 2017 dengan melibatkan sembilan lembaga PIAUD di Yogyakarta. Pendekatan penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data berupa wawancara, observasi dan dokumentasi. Data-data yang terkumpul dianalisis secara deskriptif, interpretatif, dan komparatif berlandaskan teori-teori pembelajaran neurosains. Hasil penelitian menunjukkan bahwa PIAUD di Yogyakarta dapat dipetakkan menjadi tiga, yakni PIAUD robotik, akademik dan saintifik. PIAUD robotik adalah PIAUD yang beresiko merusak otak anak karena melakukan mal praktik pembelajaran (calistung & BTAQ). PAUD akademik adalah PIAUD yang beresiko membonsai otak anak karena semua kegiatan pembelajaran hanya diorientasikan pada penguasaan calistung dan hafalan Alqur’an. PIAUD Saintifik adalah PIAUD yang berorientasi pada optimalisasi potensi otak anak, karena semua kegiatan pembelajaran disusun berdasarkan karakteristik perkembangan dan cara kerja otak anak.